Key Characteristics of Nitrous Oxide-Induced Neurological Disorders and Differences Between Populations - Zhang, Juanjuan; Xie, Dandan; Zou, Yanfeng; Yu, Xuen; Ji, Yang; Wang, Chengyou; Lv, Xinyi; Zhou, Nong; Jiang, Xiao; Wang, Kai; Tian, Yanghua (Frontiers in Neurology, 2021)
Background: Nitrous oxide (N2O), commonly known as laughing gas, is inhaled recreationally because it produces the feelings of euphoria and freedom from pain. The risk of neurological dysfunction secondary to N2O abuse and its clinical diagnosis are, however, not yet sufficiently recognized, especially in China. Here, we have summarized the key clinical characteristics of N2O-induced neurological disorders. Materials and Methods: We recruited 20 patients with N2O-induced neurological disorders and analyzed their clinical features, laboratory data, magnetic resonance imaging and electromyography. We also carried out a literature review and compared 99 previously reported patients with our case series to confirm our results. Subgroup analysis was performed to explore the difference in demographical and clinical characteristics of N2O abuse between Asian and non-Asian patients. Results: The most common initial symptoms of N2O-induced neurological disorders were weakness and/or paresthesia. Most patients presented with myelopathy and/or peripheral neuropathy. The most commonly involved segment of the spinal cord was the cervical spinal cord, extending over 4–6 vertebral levels, but more than half of the patients with myelopathy had no sensory change at the corresponding spinal level. Homocysteine was found to be the most sensitive and practical indicator for diagnosis. Subgroup analysis showed that the Asian patients (median:22.0 years old, Q1-Q3:19.0–26.0 years old) with N2O abuse were younger than non-Asian patients (26.0 (22.3–31.0) years old, P=2.8×10-4). The incidence of myelopathy combined with peripheral neuropathy was significantly higher in Asian patients than in non-Asian patients, who had myelopathy or peripheral neuropathy (P = 2×10-5). Conclusions: Key clinical characteristics of N2O abuse are longitudinally extensive cervical myelopathy and peripheral neuropathy. Recognition of these traits in young people in the age group of 20-30 years will provide important guidance for accurate diagnosis of neurological disease associated with N2O abuse. The clinical manifestations differ in Asian patients and non-Asian patients.